Big Bang Cosmology Reinterpreted - Paulo Aguiar (Newest Updates in Physical Science Research Vol. 6, 2021)
In this chapter, we show how the inhomogeneity in the matter distribution created until the time of thelast scattering surface in the light of some spatially homogeneous but anisotropic models, created anisotropies that on large angular scales (larger than \(ϑ 2^ °\)) not differ from those considered in Friedmann-Lemaitre-Robertson-Walker (FLRW) geometries. The mark left in the cosmic microwave background radiation by variations density primordial, in the form of a fractional variance in the temperature of this radiation, is controlled by the same expression used by FLRW models for these anisotropic models. The classical Sachs-Wolfe effect is recovered under adiabatic initial conditions, since the anisotropy of the global expansion is minimal at the time of the last scattering surface. This conclusion is consistent with previous work on the same anisotropic models, in which the Hubble parameters along orthogonal directions are considered to be roughly equal to the current present epoch, and the observations are unable to differentiate them from the FLRW models. The current values of the anisotropic parameters imposed by COBE observations were used to determine upper limits.